(untitled) - Baco, M.N.=700 1 Tostain, S.; Mongbo, R.L.; Dainou, O.; Agbangla, C.
(En, Fr, Es)
ilus., 15 ref.
Keywords: DIOSCOREA CAYENENSIS; RECURSOS GENETICOS; CONSERVACION DEL GERMOPLASMA; EROSION; GENETICA; ITALIA